The Relationship between Screen Time and Speech and Language Development in 3-6 Years Children - Annisa, Lale Hurun ‘In; Rukmana, Bq Fitrihan; Wahyudi, Iwan; Amrullah, Muhammad (THRIVE Health Science Journal, 2025)
Screen time activity in children at developmental age has an important positive and negative influence. Currently, screen time has become a habit for children in their daily activities, so it is not uncommon to find children with high and excessive screen time habits. This can affect the growth and development of children in various aspects, one of which is speech and language development. This study aims to determine the relationship between screen time and speech and language development in children aged 3-6 years in Ketara Village. This research uses a cross-sectional method with a quantitative approach. The population in this study is 261 children aged 3-6 years. The sampling method in this study uses purposive sampling with a sample size of 72 children. The hypothesis analysis of this study uses chi-square analysis. The research results show that most respondents experience a high level of screen time habit, with 37 children (51.4%), and most children with speech and language development measurements using the DENVER II observation sheet, 42 (58.3%) children experience suspect development. The Spearman rank correlation test result obtained a Chi-Square value with a significance level of < 0.001 (p-value < 0.05), which means that Ha is accepted, so it is concluded that there is a significant relationship between Screen Time and Speech and Language Development in Children Aged 3-6 Years in Desa Ketara.